Bayer-geopolymers: An exploration of synergy between the alumina and geopolymer industries - Van Riessen, Arie; Jamieson, E.; Kealley, Catherine; Hart, Robert; Williams, Ross (Elsevier BV, 2013)
Previously, caustic residues such as red mud and sodium oxalate have been used to provide filler and as a supplementary source of alkali for geopolymers. However, rather than incorporation of dilute alkali residues within geopolymer precursors, a significant counter-intuitive approach is to synthesise geopolymers using Bayer process liquors as a primary source of caustic sodium aluminate and to add locally available fly ash as a source of reactive silica and additional alumina.In addition to the potential for using significant quantities of industrial residues to manufacture geopolymers, these relatively new cements have the ability to bind a range of contaminants. As the Bayer process could achieve significant process impurity removal by utilisation of plant liquor, synergy between the alumina and geopolymer industries could be achieved.Geopolymers with a Si/Al ratio of 2.3 and a Na/Al ratio of 0.8 were targeted. With only synthetic plant liquor as the alkali activator, geopolymers with a mean compressive strength of 33 MPa were synthesised, while use of processed plant liquor resulted in compressive strengths of 43 MPa.